Fantastic Four : Unthinkable - Waid, Mark, 1962- (Fantastic Four, 2025)
One of the greatest creative pairings on FANTASTIC FOUR since Stan Lee and Jack Kirby, Mark Waid and Mike Wieringo brought Marvel's First Family into a golden era - and straight into one of their most monumental showdowns with the greatest foe, Doctor Doom! The Fantastic Four's arch-nemesis, Doctor Doom, has leveled up by doing the unthinkable! But what great sacrifice did Doom make to gain his frightful power - and his terrifying new armour? Victor strikes at the very heart of Marvel's First Family by targeting the children of Reed and Sue Richards. To save Franklin and Valeria from their fates, the FF must fight harder than ever before - and Mister Fantastic, ever the scientist, must force himself to learn and believe in magic! Even if they survive this deadly encounter, the emotional scars left will not be gone anytime soon - so what can the Thing do to help? Collecting: Fantastic Four (1998) 67-70, 500-502.